A Dielectric Model of Self-Assembled Monolayer Interfaces by Capacitive Spectroscopy - Goes, Marcio S. [UNESP]; Rahman, Habibur; Ryall, Joshua; Davis, Jason J.; Bueno, Paulo Roberto [UNESP] (Amer Chemical Soc, 2012)
The presence of self-assembled monolayers at an electrode introduces capacitance and resistance contributions that can profoundly affect subsequently observed electronic characteristics. Despite the impact of this on any voltammetry, these contributions are not directly resolvable with any clarity by standard electrochemical means. A capacitive analysis of such interfaces (by capacitance spectroscopy), introduced here, enables a clean mapping of these features and additionally presents a means of studying layer polarizability and Cole-Cole relaxation effects. The resolved resistive term contributes directly to an intrinsic monolayer uncompensated resistance that has a linear dependence on the layer thickness. The dielectric model proposed is fully aligned with the classic Helmholtz plate capacitor model and additionally explains the inherently associated resistive features of molecular films.